Resolução das contradições e a evolução da atividade no processo de desenvolvimento de produtos (PDP) : uma abordagem a partir da teoria da atividade - Baumgartner, Luis Fernando (2016)
The escalation of the competitiveness in the auto parts segment has been driving their companies to deep search better results. In this scenario, the product development process (PDP) has been of paramount importance. With its multidisciplinary characteristic, it articulates simultaneously different rationalities and actors who have built on very different interpretations of their real work. Interventions aiming to enhance the PDP performance inside an organization focus on the evaluation and modification of the prescribed work. When this is the approach, they limit their scope on the evaluation of the procedures and stated workflows and use a deterministic assumption which imposes just one single way to have the work done. This research proposes the Activity Theory as an adequate theoretical framework to deal with work redesign and shed light on the results from a case study where the first stage of the PDP was studied. We concluded that the activity system model proposed by Engeström identifies and reveals contradictions, which once in the equation, can really enhance PDP performance.